Rino-orbital-cerebral Mucormicosys in A Patient Type 1Diabetic: A Case Report - Marpaung, Hamka Gunawan; Baso, Gery Dala Prima; Rizka, Aulia; Nelwan, Erni Juwita; Wardani, Retno S; Wahyuningsih, Retno (UI Scholars Hub, 2018)
Mucormycosis is an opportunistic andfrequently fulminating fungal infection causedby members of the family Mucoraceae, orderMucorales and class Zygomycetes which highly invasive and high mortality. Mucormycosis occurs in diabetic patients with poor blood glucose control. We reported a case of rhinocerebral mucormycosis in 20-year-old female patient with type 1 diabetes. The patient was treated for diabetic ketoacidosis and swollen symptoms in the left eye and out secretions from the left nose containing blackish spots. The probable diagnosis of rhinocerebral mucormycosis is made based on the results of direct examination and culture of nasal and palate tissue biopcywhich result suitable for Mucor sp. She was given systemic antifungal therapy with amphotericin B and symptoms of swelling of the left eye and secretions of the left nose with patches of blackness improved.